Determinan Ketimpangan dan Kemiskinan dalam Kerangka Pembangunan Ekonomi Inklusif (Studi Pada Kabupaten/Kota di Nusa Tenggara Timur ) - Dyonisius H S Jewaru; Ervina Jayanti Siagian (Badan Pusat Statistik Provinsi NTT, 2022)
Economic development is currently moving from a pro-poor growth paradigm to inclusive economic development. Its main sub-pillars include reducing inequality and reducing poverty. These indicators are quite complex and multidimensional. NTT Province is in the top 5 provinces with the lowest inequality and poverty reduction index in Indonesia. The main problem is the slow growth of inequality and poverty reduction. In addition, there is a large gap in inequality and poverty between regencies/cities compared to NTT and national figures. This study aims to analyze the determinants of reducing inequality and poverty within the framework of inclusive economic development in all regencies/cities and underdeveloped regencies in NTT in 2015-2021. Regression analysis of panel data using a fixed effect model found that the significant factors that determine inequality reduction are economic growth, economic infrastructure, and expansion of access and opportunities. However, economic growth does not significantly affect the reduction of inequality in underdeveloped districts in NTT. Meanwhile, significant factors that determine the level of poverty reduction are job opportunities, economic infrastructure, and expansion of access and opportunities